VIEWING POSTMODERN AMERICAN YOUTH SOCIETY THROUGH UGLIES AND THE HUNGER GAMES: A TURN FROM NOSTALGIA TO ESCAPE - Anna Sri Astuti (Rubikon : Journal of Transnational American Studies, 2022)
At the turn of the 21st century, Americans experienced the shift from the Modern Era to the Postmodern Era. The Modern Era that worships technology blurs the borders between countries. Technology and transportation, as the major components of the revolution in the globalization era, have labeled the planet a ‘global world’. This study found out that the Internet, for instance, has made access among countries possible. One of the effects of this movement towards globalization is the erosion of American exclusivity. Apart from its positive contributions to the world, technology has produced world chaos and destruction. The attacks on the World Trade Center and Pentagon in 2001 and the economic crisis in 2008 are two fatal catastrophes that hit America in the 21st century and caused major trauma to the American people. This study is conducted to analyze postmodern American youth society through the analysis of Uglies and The Hunger Games to see how American youth make a turn from a victorious nostalgia to an escape from reality and create their own imaginary worlds through dystopian literature in response to what is happening in America. Using the theories of Postmodernism, small narratives from the data of the two novels are collected to reveal what are implicitly stated in the two novels.